The importance of being Earnest and other plays - Wilde, Oscar (Oxford : Oxford University Press, 2008)
Oscar Wilde was already one of the best known literary figures in Britain when he was persuaded to turn his extraordinary talents to the theatre. This is the only fully annotated edition of Wilde's major plays, which spearheaded the dramatic renaissance of the 1890s and retain their power today.[BOX TO GO ABOVE PLAYS] Under the General Editorship of Dr Michael Cordner of the University of York, the texts of these plays have been newly edited and are presented with modernized spelling and punctuation. In addition, there is a scholarly introduction and detailed annotation.
Keywords: Identity (Psychology) -- Drama; Foundlings -- Drama; Drama. -- England